Status of association studies linking diabetes mellitus and periodontal disease in India - Acharya, Anirudh B. (Medknow Publications, 2010)
BACKGROUND: The prevalence of diabetes mellitus (DM) and periodontal disease / periodontitis (PD) is high, and the association of these two as risk factors influencing each other has been recognized and is extensively documented. However, a majority of these association studies have been done in developed countries and / or in developing countries other than India. OBJECTIVE: To review, quantify and qualify the status of the published indexed scientific literature regarding the bidirectional association of DM and PD in India. METHOD: An internet search of the literature was conducted to examine relevant association studies of DM and PD in India. As a matter of interest, the related articles were searched manually from one non-indexed national (India) publication of periodontology until October 2008. Specific focus was on indexed literature and only these were considered for the review. RESULT: Eleven pertinent indexed publications addressing the concern with regard to population in India were identified. Most of them were in agreement with the accepted mechanisms involving these two diseases, but more supported a unidirectional view of interaction, that is, advocating the role of DM in a worsened periodontal condition. One study with an opposite view was recognised. CONCLUSION: The paucity of such research in India, which will be a hub of diabetics in the near future, reflects the need to make available a strong body of evidence in the indexed literature relating not only to DM and its ‘sixth complication’, PD, but also the strong influence of PD on DM.